COVID -19 pandemic, surveys on elderly about vaccination. National and European perspectives - Bałandynowicz-Panfil, Katarzyna; Olah, Șerban; Pék, Győző; Kaszás, Adrienn; Őrsi, Balázs (Magyar Gerontológia, 2021)
A summary of Symposium titled COVID-19 pandemic, surveys on elderly about vaccination reserved in this abstract. The severe cases of COVID-19 in Europe. A comparative analysis using SHARE data base The paper focuses on the severe cases of COVID-19 in Europe and the predictors of these cases. The author used the secondary analysis of a large data base (SHARE) of persons aged 50 or more from the EU countries and the Switzerland. The data have been collected in the summer of 2020. In the first part the focus is on the theoretical starting point of the analysis. In the second part the main outputs are presented. How to convince the undecided - communication with the elderly and attitudes towards vaccination COVID-19 in Poland The pandemic has had its toll on the socio-economic life of most people. Governments and international organizations face new challenges in a situation of uncertainty. Social campaigns are designed to encourage as many people as possible to join the vaccination plan. Achieving population resilience requires a significant commitment of organizational, financial and communication resources. Older people constitute a priority group in the vaccination system in Poland. However, despite the measures taken, there remains a significant share of seniors who remain reluctant to vaccination. The government is taking further pro-turnout measures targeted at the elderly. The shortcomings of the existing strategies should be eliminated for the benefit of society. The aim is to summarize the research conducted in the field of the needs and possibilities of communication with the elderly, attitudes towards vaccinations and sources of influence on making purchasing decisions of seniors. Vaccination attitudes – international project in Central and Eastern Europe The beginnings of the project date back to 2020. The uncertainty that became commonplace in the times of the pandemic indicated new areas of previously unknown dependencies. Stress, uncertainty, attitudes towards the threat, protective behaviour, and soon also attitudes towards vaccination seemed the most important at that time. Examining the existing dependencies would allow a better understanding of the phenomenon of social responses to the pandemic and would support governmental and non-governmental, national and international actions that would be an important tool in the fight against the negative consequences of a spreading COVID-19. Scientists from Central and Eastern European countries representing different disciplines (sociology, economics, communication, statistics, psychology and psychiatry) joined forces in a common international project investigating the relationship between attitudes towards vaccines and the level of perceived mental health, uncertainty, socio-demographic variables and the level of religiosity. Core aims of the project were to analyse the model of predictors concerning demographic, psychological, and social factors influencing the intention to vaccinate against COVID-19 and to provide the information to prepare and implement more effective and efficient health messaging strategies and campaigns targeting groups reluctant to COVID-19 vaccination in Eastern and Central European countries. The project involved the development of a common research tool - a questionnaire, parallel research in four countries of Central and Eastern Europe (Poland, Romania, Slovenia, Hungary), more than 2000 respondents (unvaccined adults) and joint development of the results of the analysis, using the potential of all involved partners. The project is still developed to next stages of investigation. Results will be published in high quality journals in years 2022 and 2023. Partners involved represent: University of Gdańsk (Poland), University of Oradea (Romania), University of Ljubljana (Slovenia), University of Debrecen (Hungary). More information: k.balandynowicz@ug.edu.pl. Survey on unvaccinated Hungarian elderly people during the COVID-19 pandemic During the pandemic, we performed a comparative study of the Hungarian unvaccinated people, focusing on psychological and demographic aspects in our questionnaire. The survey data collection lasted from 27 August to 13 October 2021. Participants were over 18 years of age who have not yet received any vaccination against the COVID-19 virus. The method used is an on-line questionnaire survey. The survey is not for political but for scientific purposes, and we hope that its results will contribute to a more professional management of the COVID-19 epidemic. The survey of Hungarian team was conducted in collaboration with Polish, Slovenian and Romanian university researchers. The test dimensions are as follows: Well-being at the time of pandemic (happiness, health.) Depression, Anxiety and Stress Scale (DASS21) Vaccination Attitudes Examination Scale (VAX) Sources of information about vaccination Religiosity level Demographics (metrics) The presentation focuses on the most important aspects of the first analysis of the Hungarian results. The study involved 478 people: 113 men, 363 women, and 2 people identified as “other”. It is worth highlighting from the first processing of the data that a large number of unvaccinated people do not believe that they are at risk of getting the COVID-19 virus. In our sample 42% of the unvaccinated are very sure that the vaccine will not work, and 30.6% are afraid that they will become infected because of the vaccine. They do not usually feel safe after vaccinations, they are afraid of the undiscovered consequences, and they trust more in their natural immunity. 61.8% definitely do not want a vaccine for themselves, nor in the future. 67.3% want to wait to see how vaccines work in other people. During processing, we could identify the ones with a definite anti-vaccination attitude. They were also analyzed on the basis of their political affiliation, religiosity, and place of residence. Regarding the DASS-21 depression subscale, the young age group scored significantly higher than the elderly. According to the DASS-21 stress subscale, the value belonging to young people is significantly higher than that of older people. On the Vaccination Attitudes Examination (VAX) Scale’s concerns about financial profiteering subscale, seniors scored significantly higher. Interpreting our results in the context of parallel international studies is also part of our objectives. Our results provide an opportunity to serve important aspects for the communication strategies with unvaccinated elderly.